2022
DOI: 10.3390/mi13101624
|View full text |Cite
|
Sign up to set email alerts
|

Convective Heat and Mass Transport in Casson Fluid Flow in Curved Corrugated Cavity with Inclined Magnetic Field

Abstract: Convection in fluids produced by temperature and solute concentration differences is known as thermosolutal convection. It has valuable utilization in wide industrial and technological procedures such as electronic cooling, cleaning, and dying processes, oxidation of surface materials, storage components, heat exchangers, and thermal storage systems. In view of such prominent physical significance, focus is made to explicate double (thermal and solutal)-diffusive transport in viscoelastic fluid characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The convective flow of non-Newtonian liquids in closed chambers has been investigated in several studies performed throughout the past decade [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Pop and Sheremet [ 21 ] studied the radiative and buoyant convection of CF in a bounded domain with the existence of viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…The convective flow of non-Newtonian liquids in closed chambers has been investigated in several studies performed throughout the past decade [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Pop and Sheremet [ 21 ] studied the radiative and buoyant convection of CF in a bounded domain with the existence of viscous dissipation.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the study revealed the impact of double diffusion and Casson fluid behavior on the flow and temperature distributions within the enclosure. Shah et al [7] analysed the behavior of Casson fluids in a curved corrugated cavity and the influence of convective heat and mass transport.…”
Section: Introductionmentioning
confidence: 99%